A mechanochemical model for adult dermal wound contraction and the permanence of the contracted tissue displacement profile. - Olsen, L; Sherratt, J; Maini, P (1995)
The healing of adult mammalian skin wounds involves a complex sequence of spatially and temporally coordinated processes. Wound contraction, by reducing the size of the injury, is an intrinsic component of full-thickness excisional dermal wound healing. The underlying biomechanics of wound contraction, however, are not fully understood, and little is known about the pathogenesis of severe medical conditions known as fibrocontractive diseases. The aim of this work is to investigate a deterministic mathematical model in order to obtain insight into the mechanistic relationships between wound contraction and associated normal and pathological healing processes. The model describes the essential roles of fibroblast and myofibroblast cells, a chemical growth factor and the extracellular matrix which includes type I collagen. The model results are qualitatively consistent with the biology of fibroplasia and wound contraction. It is shown that a contracted state evolves during a (long) transient phase of healing known as "proliferation", while collagen kinetics are fundamental to the considerably longer "remodelling" phase. Some quantitative results, notably on the evolution of wound contraction, compare favourably with experimental data. Application of the model to adult human dermal wound healing in vivo, with a greater understanding of the underlying biological mechanisms involved, may suggest strategies for controlling contraction and fibrocontractive diseases.